Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Berbantuan Quizizz terhadap Hasil Belajar Siswa pada Materi Aritmatika Sosial - M. Riyadul Hamdi; Tri Novita Irawati; Tri Susillaningtyas (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Low student achievement in mathematics is often attributed to unengaging and less interactive teaching methods. The Teams Games Tournament (TGT) learning model, when integrated with Quizizz, offers a cooperative and gamified learning environment that can enhance student motivation and academic performance. This study investigates the effectiveness of the TGT model supported by Quizizz in improving students' learning outcomes in the topic of social arithmetic. Employing a quantitative approach with a One-Group Pretest-Posttest design, the study involved 24 seventh-grade students from MTs Al-Ma’arif Wuluhan. Data were collected through pretest and posttest assessments and analyzed using descriptive statistics, normality testing with the Shapiro-Wilk test, and a paired sample t-test. The results revealed a significant improvement in students' average scores from 47.92 to 82.71, with a p-value < 0.001, indicating a statistically significant effect of the implemented learning model. These findings support the use of TGT with Quizizz as an effective and engaging alternative for mathematics instruction.